Peningkatan Kemampuan Keterampilan Menulis Puisi dengan Memanfaatkan Media Audio Visual Siswa Kelas VII UPTD SMP Negeri 8 Gunungsitoli - Zebua, Yogi Chris James; Waruwu, Lestari (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research was motivated by the fact that Indonesian language skills were still low or below average among class VII students at UPTD SMP Negeri 8 Gunungsitoli, especially the ability to write poetry. The purpose of this research is to measure the increase in poetry writing sills by utilizing audio visual media. The method used is a description method using a classroom action research (PTK) design. Based on hasti in the learning carried out by teachers, more than 75% of students got a score below the minimum criteria (KKM), namely 75. Seeing this condition, it is necessary to discuss the use of certain learning media to improve students abilities in learning poetry writing in class VII students at UPTD SMP Negeri 8 Gunungsitoli middle schools, the media chosen was audio visual media, the increase in students ability to write poetry can be seen in the result of the first cycle of research which obtained a total of 1.630 whit an average of 36 and 12 people were declared to have passed the KKM (75). In the second cycle the student’s ability to write poems after using the audio-visual media obtained an increase with several 2.380 with an average of 82, zelush cycle 1 and ll can be seen with several 150 and an average of 26. Based on this, awayang is categorized as complete in actus learning, has research 100%. After the research was carried out, it could be concluded that the use of visual audio media could improve the remaining abilities in writing putat